Polyurethane foams based on vegetable oils and polysaccharides of natural origin - Savelyev, Yu.V.; Akhranovich, E.R.; Markovskaya, L.A.; Yanovych, I.V.; Dmitrieva, T.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
New polyurethane foams comprising both vegetable oils and polysaccharide in a macrochain have been synthesized. The simultaneous presence of two natural compounds allows one to increase the hydrophilicity and the ability to a degradation under environmental conditions, while maintaining the basic performance properties.